Efficacy testing of ‘soft’ pesticides for cabbage butterfly (Pieris brassicae nepalensis Doubleday) in cauliflower at Rampur, Chitwan - Giri, H. N.; Sharma, M. D.; Thapa, R. B.; Pande, K. R.; Khatri, B. B. (Journal of Agriculture and Forestry University, 2020)
Cabbage butterfly (Pieris brassicae nepalensis) is an important pest of cabbage, cauliflower, and many other crucifers. Pesticide use is a popular method of pest management in small and large-scale vegetable farming in Nepal. These practices are directly linked to human health, biodiversity, and the environment. There are various categories of pesticides available in market, some are toxic, and some are ‘soft’ in nature. Chemical action of pesticides to the insect pest has been recommended by efficacy testing. Accordingly this research was done to evaluate the effectiveness of ‘soft’ chemicals against cabbage butterfly management. Cauliflower cultivar ‘Snow Mystique’ was used for the field experiment established at Agriculture and Forestry University (AFU), Rampur Chitwan during November 2017 to March 2018. Six common pesticides such as Mahashakti (Bt. based), Neemix (Azadirachtin based), Spinosad (bacteria based), Liquid manure (mixture of botanical, cow urine and other ingredients), Superkiller-10 (Cypermethrin based), and control (no use) were used in Randomized Complete Block Design (RCBD), each with four replication. The study findings revealed that the highest number of larval populations of cabbage butterfly as well as damaged plants, leaves, curds, and holes were recorded in control plot, and the lowest larval population and damages were recorded in Cypermethrin and Spinosad treated plots. On the other hand, curd height was significantly higher (13.9 cm) in liquid manure treated plot that was similar with Spinosad treated plots. There was no significant difference in curd diameter (23.1 cm) and biological yield (79.6 t/ha) in Spinosad and Cypermethrin treated plots. It is thus suggested that biological pesticide, such as Spinosad are superior in controlling pests of cauliflower than other tested pesticides. These pesticides along with other soft pesticide are potentially safer for vegetable production. This information is important to develop IPM protocol for cabbage butterfly management in crucifers.